ABSTRACTS XV SYMPOSIUM OF RESEARCH. FACULTY OF HEALTH UNIVERSITY OF VALLE OCTOBER 23-25, 2013. CALI, COLOMBIA - UNIVERSIDAD DEL VALLE, PROGRAMA EDITORIAL (GastrohNup, 2016)
ABSTRACTS XV SYMPOSIUM OF RESEARCH. FACULTY OF HEALTH UNIVERSITY OF VALLE OCTOBER 23-25, 2013. CALI